2020
DOI: 10.1016/j.yebeh.2020.107188
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms and prevention of acid reflux induced laryngospasm in seizing rats

Abstract: Objective: Recent animal work and limited clinical data have suggested that laryngospasm may be involved in the cardiorespiratory collapse seen in sudden unexpected death in epilepsy (SUDEP). In previous work we demonstrated in an animal model of seizures that laryngospasm and sudden death were always preceded by acid reflux into the esophagus. Here, we expand on that work by testing several techniques to prevent the acid reflux or the subsequent laryngospasm. Methods:In urethane anesthetized Long Evans rats w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 69 publications
4
14
0
Order By: Relevance
“…As seen in Figure 3c-e seizure activity increases over a period of 60 min after KA injection, with increasing power of high frequency EEG signals. Similar to previous studies[20,21,37] we observe that KA can significantly change breathing patterns (Figure 3f). We see an increase in respiration rate from baseline (80.6 ± 20.8 breaths/min) to a rapid, irregular rate (140.5 ± 67.6/min).…”
Section: Resultssupporting
confidence: 92%
See 3 more Smart Citations
“…As seen in Figure 3c-e seizure activity increases over a period of 60 min after KA injection, with increasing power of high frequency EEG signals. Similar to previous studies[20,21,37] we observe that KA can significantly change breathing patterns (Figure 3f). We see an increase in respiration rate from baseline (80.6 ± 20.8 breaths/min) to a rapid, irregular rate (140.5 ± 67.6/min).…”
Section: Resultssupporting
confidence: 92%
“…MRI scans also revealed that for surviving rats, there was no detectable stomach fluid in the esophagus (6 out of 11 animals). This further strengthens the hypothesis of acid reflux having a causal relationship with sudden deaths and aligns well with our previous observations[20,37].…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…For all calculations and analysis, t = 0 was set at the start of the mist. In a procedure similar to prior work, 38 chemoreflex rats were mounted supine in a stereotaxic frame with a 3D printed feeding tube inserted into the mouth. A laryngoscope mounted on a GoPro camera modified by the company BackBone visualized the larynx.…”
Section: Methodsmentioning
confidence: 99%